2013
DOI: 10.1002/bsl.2081
|View full text |Cite
|
Sign up to set email alerts
|

Adult Eyewitness Memory and Compliance: Effects of Post‐event Misinformation on Memory for a Negative Event

Abstract: This study investigated effects of misleading post-event information, delay, and centrality definition on eyewitness memory and suggestibility for a negative event (a vividly filmed murder). Either immediately or 2 weeks after viewing the film, 93 adults read a (misleading or control) narrative about the event and then completed a recognition memory test. Misinformation acceptance was operative, but strong evidence for memory malleability was lacking. Compliance predicted misinformation effects, especially on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Even though many memory skills are relatively well developed by 9 years of age (Bjorklund, 2011), in the present study, younger children produced more commission errors to the direct questions than did older children. The age difference might reflect poorer memory or greater compliance in younger than in older individuals (e.g., Cassel, Roebers, & Bjorklund, 1996;Lee, 2004;McCloskey & Zaragoza, 1985;Paz-Alonso, Goodman, & Ibabe, 2013), and underscores the problem of asking direct (e.g., yes-no) questions when interviewing children about their memories (Peterson, 2012), although in the present case, the memories only concerned a relatively brief, positive video clip. Second, higher levels of psychopathology, above and beyond maltreatment history, were significantly related to children's memory error for positive information.…”
Section: Discussionmentioning
confidence: 81%
“…Even though many memory skills are relatively well developed by 9 years of age (Bjorklund, 2011), in the present study, younger children produced more commission errors to the direct questions than did older children. The age difference might reflect poorer memory or greater compliance in younger than in older individuals (e.g., Cassel, Roebers, & Bjorklund, 1996;Lee, 2004;McCloskey & Zaragoza, 1985;Paz-Alonso, Goodman, & Ibabe, 2013), and underscores the problem of asking direct (e.g., yes-no) questions when interviewing children about their memories (Peterson, 2012), although in the present case, the memories only concerned a relatively brief, positive video clip. Second, higher levels of psychopathology, above and beyond maltreatment history, were significantly related to children's memory error for positive information.…”
Section: Discussionmentioning
confidence: 81%
“…They rated the extent the stimulus (a) represented their native setting and (b) represented a crime scene. Consistent with Paz‐Alonso, Goodman, and Ibabe (), the mid‐rating score was used in deciding whether a stimulus received sufficient rating. The stimuli settings were rated by participants to adequately represent settings in their respective countries (Ghanaian stimuli— M = 3.79, SD = .97; Dutch stimuli— M = 3.33, SD = .62) and reflect plausible crime scenes (Ghanaian stimuli— M = 3.43, SD = 1.28; Dutch stimuli— M = 3.47, SD = .83).…”
Section: Methodsmentioning
confidence: 99%
“…The misinformation paradigm typically involves recognition tests (e.g., Calvillo, Parong, Peralta, Ocampo, & Van Gundy, ; Paz‐Alonso, Goodman, & Ibabe, ). Prior studies (Francis & Gutiérrez, ; Francis & Strobach, ) reported that bilinguals' recognition memory is higher in their second language (L2) than in their first language (L1).…”
Section: Bilingual Memorymentioning
confidence: 99%